Pengaruh Penerapan Metode Tilawati Terhadap Pembentukan Karakter Peserta Didik Kelas VI SDN Dapurkejambon 3 Jombang - Siti Imrohah; Shofwatal Qolbiyyah; Adibah Adibah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2024)
Studying the Al-Quran can improve abilities and habits that are commendable, therefore this research aims to find out the relationship between learning to read the Al-Qur'an. Quran by applying the tilawati method to build the character of students at SDN Dapurkejambon 3 Jombang This research is a quantitative research with variables of the tilawati method and character formation of students at SDN Dapurkejambin 3 Jombang. Data collection was carried out by distributing questionnaires about character formation, then analyzing it to determine the influence of variable X on variable Y. Based on data analysis, the results obtained are (1) the application of the tilawati method at SDN Dapurkejambon 3 Jombang is in the good category (2) the tilawati method has a significant positive effect on the formation of student character with the result of the tilawati method variable (X) obtained t_count= 95.458 which is greater than t_tabel= 1,691, and a significance value of 0.000 <0.05 Key word: Tilawati Method; The Character of Students